Karakter Pelayan Tuhan di Tengah Arus Postmodernisme Berdasarkan 2 Timotius 2:2-6 - Robert Stefanus Hia (Jurnal Ilmiah Tafsir Alkitab, 2024)
This study aims to investigate the meaning and implementation of the character of a servant of God based on 2 Timothy 2:2-6 in the context of the development of the postmodernist movement. In 2 Timothy 2:2-6, Paul emphasizes the importance of the character of a good servant of God, amidst the onslaught of the spirit of relativism and individualism in the postmodern era. Although this teaching has been around for centuries, there is still a gap in understanding and application in today's church ministry. This study uses a qualitative approach with the epistolary genre exegesis method and literature study. The results of the study indicate that the character of a servant of God must be post-individualistic, meaning that a servant of God must remain social even though he does not agree with the spirit of individualism. The character of a servant of God must also be post-rationalistic, meaning that even though he does not agree with the spirit of relativism, it does not make the servant of God "gray" in thinking or "anti-intellectual." In conclusion, 2 Timothy 2:2-6 provides a deep understanding of the principles of the character of a servant of God for the church of God in facing the challenges of the postmodernist movement.